A multidisciplinary approach to game day preparation for team sports: a delphi study with expert consensus - Mason, B. R.; Pumpa, K. L.; McKune, A. J.; Gill, N. D.; Ball, N. B. (The Journal of Strength and Conditioning Research, 2022)
The aim of this study was to identify game day preparation strategies used by performance staff to improve team sport performance and to determine consensus regarding the application and importance of these strategies. Twenty-five performance staff working in high performance or professional team sports participated in this Delphi study, which implemented 3 survey rounds. The first round sought responses to open-ended questions relating to the use of game day preparation strategies. These responses were developed into statements and recirculated (round-2 survey), with subjects asked to rate their level of agreement with each statement. The third and final survey presented revised versions of statements that did not reach a consensus in the previous round, along with new statements derived from subject responses. A thematic analysis of the open-ended responses in the first survey identified 5 key themes relating to game day preparation strategies: "exercise," "nutrition," "psychological," "technical and tactical," and "other." The round-2 survey included 38 statements across the 5 themes, with 22 reaching the consensus threshold (=75%) for agreement. The remaining 16 statements did not reach consensus. The final survey included 18 statements (16 revised and 2 new) with 12 reaching the consensus threshold for agreement. Key preparation strategies identified in this study include structured and progressive warm-ups, strength and power-based priming sessions, individualized nutrition plans, and precooling in hot conditions. Performance staff working in similar environments should consider adopting these strategies to improve athlete or team performance.